The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1177/147078539904100306
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Older People in Advertisements: Ageism in Advertising

Abstract: This paper discusses the criticism that has been targeted at the advertising industry about its hesitancy to use older models in advertising. It reports research on this issue in the context of current advertising in print media, using content analysis of British advertisements in inappropriate journals. The paper includes general discussion about ageism in advertising and its social implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…When older people are featured, lasting vitality and the absence of age-related impairments appear to dominate the idea of old age. This echoes findings by Chen (2015), amongst others, and is in clear contrast to earlier decades that promoted a grimmer outlook on ageing (Carrigan & Szmigin, 1999;Whitfield, 2001). Any age-related issues presented in current advertising are those that can be successfully managed.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…When older people are featured, lasting vitality and the absence of age-related impairments appear to dominate the idea of old age. This echoes findings by Chen (2015), amongst others, and is in clear contrast to earlier decades that promoted a grimmer outlook on ageing (Carrigan & Szmigin, 1999;Whitfield, 2001). Any age-related issues presented in current advertising are those that can be successfully managed.…”
Section: Discussionsupporting
confidence: 66%
“…The second major manifestation of ageism in the media is the neglect of older people altogether, both within fictional and factual media content. For advertising, several studies in the UK have found an under-representation of older characters compared to other age groups and/or older people's share of the British population (Carrigan & Szmigin, 1999;Whitfield, 2001;Simcock & Sudbury, 2006;Chen, 2015;Olsen & Scott, 2021). Evidence supports the notion of a link between under-representation in the media, including advertising, and ageism within wider society (Kessler, Schwender & Bowen, 2010;Prieler, Kohlbacher, Hagiwara & Arima, 2011).…”
Section: Ageism In the Mediamentioning
confidence: 92%
“…The connotations of concrete objects and physical settings presented in advertisements featuring older people were often further discussed. For example, Szmigin and Carrigan (1999) suggested that a limited range of products connote the incapacity of people in old age. Prieler et al (2015) discussed the presence of the workplace setting by pointing out various forms of activities in which older people can participate.…”
Section: A Constructionist-representation Perspectivementioning
confidence: 99%
“…The notion of older people is inconsistent across the previous studies referenced in this chapter. Older people can refer to either people aged 60 years and above(Lien et al, 2009;, or people aged 50 years and above(Chen, 2015;Prieler et al, 2015;Szmigin & Carrigan, 1999).…”
mentioning
confidence: 99%